Intuitionism and Moral Reasoning - Lariguet, Guillermo (2017)
My goal for this paper can be presented as follows: I will attempt to show that objections to intuitionism, although they are serious, do not undermine entirely its fertility for knowledge and moral reasoning. This is probably the perception of contemporary philosophers like David Enoch, Robert Audi, Russ Shafer-Landau or John McDowell. In order to fulfill the objective mentioned above, I will do the following. First, I will outline broadly two of the paradigmatic features of moral intuitionism in order to identify it as a particular metaethics doctrine. Secondly, I will summarize some of the main objections that have been raised in order to discredit the value of moral intuitionism as a source both of moral knowledge and of valid support for moral reasoning. In third place, I will try, also briefly, to explain some of the possible (not all of course) answers to the objections previously mentioned in the paper. Fourth, I will recapitulate the more fruitful aspects of intuitionism, especially in regard to moral reasoning.